2015
DOI: 10.20510/ukjpb/3/i1/89245
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Montelukast and L-Carnitine on Cyclophosphamide-Induced Lung Injury

Abstract: The major aim of this work was to study the protective effects of the cysteinyl-leukotriene antagonist montelukast (ML) and L-Carnitine (LC) against cyclophosphamide (CP)-induced pulmonary injury in experimental rats. Thirty adult male albino rats were categorized at random into five groups of 6 rats each. The first group served as normal control group. All other groups were injected once with CP (150 mg/kg, i.p.). The second group was kept as CP toxicity control group The third group was injected with ML (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In this study, LC significantly increased the levels of GSH, GST, SOD and NO. This is in agreement with a previous report on the antioxidant and free radical-scavenging properties of LC [19]. It has been suggested that LC is involved in ATP synthesis through its role in mobilization of mitochondrial fatty acids during β-oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, LC significantly increased the levels of GSH, GST, SOD and NO. This is in agreement with a previous report on the antioxidant and free radical-scavenging properties of LC [19]. It has been suggested that LC is involved in ATP synthesis through its role in mobilization of mitochondrial fatty acids during β-oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Metabolism of CPA by enzyme system (hepatic cytochrome P-450) results in production of 2 metabolites that are phosphoramide mustard and acrolein [32] . The phosphoramide mustard has cytotoxic effect on the tumour cells and acrolein has a cytotoxic effect on normal cells [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, CAR plays an important protective role against titanium dioxide nanoparticles induced -cardiac toxicity [14] . L-carnitine has antioxidant effect by multiple mechanisms as a free radical scavenger, its ability of reduction of the formation of ROS and its antiinflammatory activity [32] , but there is contraverse about the potency of the protective effect of LC. some studies reported that it can minimize the nephrotoxic effect of gentamicin [22] while other studies postulated that LC did not prevent the cisplatin nephrotoxicity [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carnitine deficiency can aggravate cardiotoxicity and it is important to monitor serum and urinary carnitine levels [30]. Carnitine supplementation showed beneficial effects in various cyclophosphamide-induced toxicities [31][32][33][34]. Cyclophosphamide administration affects the ability of the heart mitochondria to retain accumulated calcium [35].…”
Section: Pathophysiology Of Cyclophosphamide-induced Cardiotoxicitymentioning
confidence: 99%